E-Modul Berbasis Hypercontent: Upaya untuk Mengatasi Kesulitan Pembelajaran Sejarah di Masa Pandemi Covid-19 - Nuraeni Marta; Djunaidi Djunaidi; Corry Iriani (Tarikhuna: Journal of History and History Education, 2022)
This article aims to review efforts to overcome the difficulties of learning history during the COVID-19 pandemic through teaching materials in the form of hyper-content-based e-modules.  The Research qualitative methods, the main data is obtained from the results of in-depth interviews with key and core informants. Since mid-March 2020, face-to-face learning has been abolished and replaced by distance learning online. Teachers and students are forced to suddenly switch and adapt to using digital devices. This sudden change resulted in "uncertainty" in the process of implementing history learning. One of the reasons is that there are still many technologically stuttering students and teachers. For history teachers, one of the difficulties encountered during the pandemic was the difficulty of teaching the material completely. They also find it difficult to develop varied learning methods so that the material can be comprehensively understood so that students are able to interpret and use it in life. This is exacerbated by the difficulties and technical constraints often encountered in online learning. Alternative learning aids are needed to overcome this problem, especially regarding material and technical constraints. The development of hyper-content-based e-modules can be an alternative solution. Teaching materials in the form of hyper content-based e-modules are teaching materials consisting of text, images, sounds and hyperlinks packaged with a digital platform. Hypercontent-based e-modules have advantages: lightweight and easy access, so students can learn the material without being limited by space and time. In addition, hyper-content e-modules that are packaged are not only in the form of text but also include sound and images, making it easier for students to understand the material. The results showed that hyper content-based e-modules help students learn independently, can be done anytime and anywhere and lighten the burden of student learning.